Diffusion Weighted Imaging (DWI) Classification and Apparent Diffusion Coefficient (ADC) Value Tendency Based on Cerebral Glioma Grading in Patients at Dr. Soetomo General Academic Hospital in 2016-2020 - Komang Wahyu Kurniawan; Sri Andreani Utomo; Joni Wahyuhadi (AKSONA, 2023)
Highlight: Many studies conclude that the prognosis of gliomas can be determined using the DWI sequence and ADC value on MRI The correlation between DWI and ADC values with glioma grading is related to tumor cellularity, nuclear-cytoplasmic ratio, and extracellular space, which affect the movement of water molecules.   ABSTRACT Introduction: Glioma grading is crucial to know its prognosis. Magnetic resonance imaging (MRI) is used as a preoperative examination that contains diffusion-weighted imaging (DWI) sequences confirmed by an apparent diffusion coefficient (ADC) value that helps assess tissue based on water diffusion. Objective: To prove the relationship between DWI and ADC values with cerebral glioma grading in patients at Dr. Soetomo General Academic Hospital in 2016—2020. Methods: This retrospective study collected medical records and MRI files in DICOM (Digital Imaging and Communications in Medicine) format. Gender, age, tumor histopathology, and glioma grading were collected. DWI and ADC values were obtained using the RadiAnt DICOM Viewer application. The data were analyzed using descriptive and analytical statistics. The chi-square test was used to analyze the relationship of DWI with glioma grading, and the spearman rank test was used to analyze the relationship of ADC value with glioma grading. Results: The majority of 35 patients were male (54.3%), aged 31–40 years old (22.9%), and the most common histopathology was glioblastoma (37.1%), WHO grade IV. On DWI, most low-grade glioma (LGG) patients showed unrestricted diffusion, and most high-grade glioma (HGG) patients showed restricted diffusion. The ADC value of HGG was lower than the ADC value of LGG. Statistical tests showed a relationship between DWI and glioma grading (p<0.05) and a relationship between the ADC value and glioma grading (p<0.05). Conclusion: There was a relationship between DWI and ADC with glioma grading in Dr. Soetomo General Academic Hospital patients for the period 2016—2020